2020
DOI: 10.22434/ifamr2019.0115
|View full text |Cite
|
Sign up to set email alerts
|

Border effect of agricultural trade between China and the Belt and Road countries: a computable general equilibrium model analysis

Abstract: In this paper, we constructed a global trade computable general equilibrium model using the input-output table data in 2002, 2007, 2010, and 2015 to measure the border effect of the bilateral trade of agricultural products between China and the Belt and Road (B&R) countries, and designed a simulation analysis under different scenarios for the impact of the B&R initiative on China’s agricultural trade. We discovered that: (1) The border effect of agricultural product trade between China and the B&R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Tese negative indicators signal broader economic challenges and disruptions that afect trade and economic performance on a global scale [32]. Understanding the underlying reasons for negative per capita GDPs requires considering a range of economic, political, and external factors that impact trade dynamics and overall economic health in both nations [14,34].…”
Section: Factors Afecting China's Apple Exports 1997-2022mentioning
confidence: 99%
See 1 more Smart Citation
“…Tese negative indicators signal broader economic challenges and disruptions that afect trade and economic performance on a global scale [32]. Understanding the underlying reasons for negative per capita GDPs requires considering a range of economic, political, and external factors that impact trade dynamics and overall economic health in both nations [14,34].…”
Section: Factors Afecting China's Apple Exports 1997-2022mentioning
confidence: 99%
“…Teir study revealed a strong correlation between China's export fows and variables such as GDP, the Chinese language, shared border, and the belt and road initiative (hereafter BRI). Dang and Pang [14] used input-output table data from the years 2002, 2007, 2010, and 2015 in order to construct a computable general equilibrium model of global trade. Te purpose of this model was to evaluate the infuence of bilateral agricultural product trade between China and the Belt and Road (B&R) countries, which is commonly known as the border efect.…”
Section: Introductionmentioning
confidence: 99%
“…In China's context, several studies were carried out to examine the factors affecting China's exports through trade analysis (see [4,39,40]). Nonetheless, just a few research on China's agricultural exports have been discovered [26,[41][42][43]. To the best of our abilities, no academic study found in the existing literature that examines the factors affecting China's agricultural product exports at a bilateral level, as well as take other time-variant and invariant metrics, to PLOS ONE explain China's agricultural export performance.…”
Section: Plos Onementioning
confidence: 99%
“…At present, many studies on the development of related industries in the countries and regions along the Belt and Road have been carried out, and have put forward valuable policy suggestions for the sustainable development of China and the global economy. Some scholars have carried out relevant research on agriculture [3,4], manufacturing [5], and other industries in countries along the Belt and Road. In addition, many scholars have studied the development of related industries in China's provinces along the Belt and Road [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%